A Comprehensive Review of Mastocytosis From Pathophysiology to Management Strategies - Magdalena Marchaj; Bartosz Basiaga; Klaudia Żądecka-Kobiałka; Anna Putra; Karolina Bednarz; Monika Nowicka-Jasińska; Paweł Frączyk; Sara Bieniek-Zając; Sebastian Baczkowski; Klaudia Krawiec (Kazimierz Wielki University, 2024)
Introduction: Mastocytosis is a rare hematologic neoplasm characterized by the abnormal proliferation and accumulation of mast cells in various tissues. Its clinical manifestations vary widely, ranging from cutaneous lesions to systemic involvement with potentially life-threatening symptoms. Understanding the pathophysiology, diagnosis, and management of mastocytosis is crucial for improving patient outcomes.    Aim of the Study: The aim of this study was to provide a comprehensive overview of mastocytosis, including its epidemiology, risk factors, pathophysiology, clinical manifestations, diagnostic approaches, and management strategies. By synthesizing current knowledge on mastocytosis, this study aims to enhance understanding of the disease and guide clinical practice.    Description of the State of Knowledge: Mastocytosis is classified into cutaneous and systemic forms, with various subtypes based on clinical and histopathological features. Diagnosis relies on a combination of clinical suspicion, serum tryptase levels, histological examination of bone marrow biopsies, and genetic testing. Management strategies include symptomatic treatment, avoidance of triggers, and targeted therapies such as monoclonal antibodies and tyrosine kinase inhibitors. Advanced forms may require cytoreductive therapy or allogeneic hematopoietic stem cell transplantation (alloHSCT).    Conclusions: Despite advancements in diagnosis and treatment, achieving lasting remission in mastocytosis remains challenging, especially in advanced cases. Further research into the molecular mechanisms underlying the disease and the development of novel therapeutic modalities are needed to improve patient outcomes and quality of life.